State and the maintenance of global anthropogenous ecological crisis - Yu. V. Oleynikov; T. V. Borzova (Юг России: экология, развитие, 2015)
Ecological crisis is a condition of bifurcation of dissipative structure (ecosystem), caused by change of its biogenic constants. In such formulation the concept of ecological crisis can be applied to ecological crises of any localization: global, regional, to ecological crises of single organism, species, biocenosis, all alive substance - biota. For any ecosystem a crisis is a condition bifurcation, i.e. infringement of dissipative structures, stable dynamic balance, ecosystem being.